THE OVARIAN RESERVE FOR WOMEN OF REPRODUCTIVE RETURN WITH POLYCYSTIC OVARY SYNDROME IN DEPENDENCE ON THE PHENOTYPE - Светлана Ивановна Елгина; Анжелика Юрьевна Беглова (The Publishing House Medicine and Enlightenment, 2018)
Objective - to determine the ovarian reserve in women of reproductive age with PCOS, depending on the phenotype. Materials and methods. 60 women of reproductive age with and without polycystic ovary syndrome were included in the study. All patients underwent general clinical, gynecological, instrumental assessment. The statistical analysis was performed using the commercially available statistical software package. Results. Statistically significant differences in the main parameters of the ovarian reserve in reproductive age women with polycystic ovary syndrome depending on the phenotype in comparison with women without polycystic ovary syndrome have been determined. Women with a basic (classical) and anovulatory phenotypes had elevated AMH levels, whereas women with ovulatory and non-androgenic phenotypes - within reference range. The volume of each ovary and the number of antral follicles were higher in women with polycystic ovary syndrome with primary (classical), ovulatory and non-androgenic phenotypes. These indicators were slightly different in women with anovulatory phenotype. Conclusion. The study of ovarian reserve in reproductive age patients with polycystic ovary syndrome will allow to more accurately determine the reproductive potential of each specific woman and influence the choice of treatment tactics. The results demonstrate the need to include the definition of AMH in women of reproductive age with polycystic ovary syndrome as an additional diagnostic criterion for the delivery of the diagnosis and determination of further management tactics.